Analysis and design of curved steel beam member in elevation using Eurocode 3 - Yandarmadi, Kelvin (Nanyang Technological University, 2021)
Curved structure existed for a long time. Its versatile characteristics make curved structures are utilized in various areas, from equipment up to large span structure such as airport terminal and bridge. Due to the technological advancement of the curved steel member, it expands the scope of structure that designer and architect can design. Although curved structure already exists for a long time, there is not much guidance from structural engineer book or code on how the curved structure behaves. Therefore, this paper presents analytical estimates of the behaviour existed by curved like structures such as curved steel beam under uniformly gravitational distributed load. This paper specifically focuses on analysing simply supported boundary condition curved beam member which pinned on the one end and roller that can be moved horizontally on the other end. This study is constituted of three parts. The first part is the formula derivation and verification of stress resultants for general arch and shallow arch for curved beam in elevation under uniformly gravitational distributed load. Secondly, the practical application and design steps for curved steel beam in elevation for five different cross-section types are studied through a design case. Thirdly, the comparison is done on the bending moment, shear force and axial force on three different boundary conditions for curved steel beam member in elevation. In the first part of the study, the obtained result based on the formula produced from the equilibrium equation is compared with the design software analysis and multiple numbers of linear segments hand calculation with similar dimension and load acting on the beam member. It shows that the general case formula that estimates the value of stress resultants (axial force, shear force and bending moment) are valid to be used as design input for a whole range of arch rise ratio. It is proven that the maximum arch rise ratio value for shallow curved is 0.0900108 with shear force as the governing factor. In the second part of the study, the design of a curved beam in elevation based on Eurocode 3 is presented on a design case for five different cross-sections.The cross-section section modulus becomes the governing factor across the beam span except for the end span near the support. It is found that that the rank based on minimum required steel is Universal Beam (UB), Universal Column (UC), Rectangular Hollow Section (RHS), Square Hollow Section (SHS), Circular Hollow Section (CHS). It is in accordance with the reduced design yield value rank among five different cross-sections. Lastly, the stress resultant results comparison between simply supported curved beam with two-hinged and three-hinged circular arch with similar dimension and loading layout are studied. The simply supported curved beam has the highest bending moment and shear force value. But on the other hand, it has the smallest axial force value. The three-hinged circular arch generally has higher axial force and shear force value than the two-hinged arch. There is no sagging moment for three-hinged circular arch. This study aspires to contribute to the database of research about the structural design of curved beam in elevation member while providing insights which can be useful to future studies.